E-learning as a tool for developing employee competencies in the corporate education system - V. V. Tonkonog; P. I. Ananchenkova (Путеводитель предпринимателя, 2020)
The article gives results of author’s study reflecting trends in Russian corporate e-learning. Massive and rapid transition of companies to remote training of employees is observed at the Russian HR-space in past few years. More and more companies are coming to the conclusion that investment in personnel development benefits the Company as a whole. Lately there has been a tendency to provide sophisticated technological products coupled with training, i.e., e-learning can become a qualitative complement of complex software products or services.